Injury risk for matched front and rear seat car passengers by injury severity and crash type: An exploratory study. (September 2015) - Mitchell, R.J.; Bambach, M.R.; Toson, Barbara
Highlights: Rear-compared to front seat car passengers are sustaining injuries of a higher severity. Rear seat car occupant protective mechanisms need examination. An objective measure of injury severity available in ED records is needed. Abstract: Background: The risk of serious injury or death has been found to be reduced for some front compared to rear seat car passengers in newer vehicles. However, differences in injury severity between car occupants by seating position has not been examined. This study examines the injury severity risk for rear compared to front seat car passengers. Method: A retrospective matched-cohort analysis was conducted of vehicle crashes involving injured rear vs front seat car passengers identified in linked police-reported, hospitalisation and emergency department (ED) presentation records during 2001–2011 in New South Wales (NSW), Australia. Odds ratios were estimated using an ordinal logistic mixed model and logistic mixed models. Results: There were 5419 front and 4588 rear seat passengers in 3681 vehicles. There was a higher odds of sustaining a higher injury severity as a rear-compared to a front seat car passenger, with a higher odds of rear seat passengers sustaining serious injuries compared to minimal injuries. Where the vehicle occupant was older, travelling in a vehicle manufactured between 1990 and 1996 or after 1997, where the airbag deployed, and where the vehicle was driven where the speed limit was ≥70 km/h there was a higher odds of the rear passenger sustaining a higher injury severity then a front seated occupant. Conclusion: Rear seat car passengers are sustaining injuries of a higher severity compared to front seat passengers travelling in the same vehicle, as well as when travelling in newer vehicles and where the front seat occupant is shielded by an airbag deployed in the crash. Rear seat occupant protective mechanisms should be examined. Pre-hospital trauma management policies could influence whether an individual is transported to a hospital ED, thus it would be beneficial to have an objective measure of injury severity routinely available in ED records. Further examination of injury severity between rear and front seat passengers is warranted to examine less severe non-fatal injuries by car seating position and vehicle intrusion.